THE INFLUENCE OF NEED FOR ACHIEVEMENT AND RISK TAKING PROPENSITY ON STUDENTS' ENTREPRENEURIAL INTENTION - Rizal Fandy Laksono; Nurjanah, Siti; Sudiarditha, I Ketut R. (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The public unemployment rate in Indonesia decreased in February as the nation's economic recovery continued. One action that can be taken is for the government to assist in funding young entrepreneurs. recognizing how much of an impact the desire for success and tendency for taking risks have on students' entrepreneurial intents at Jakarta State University. This quantitative descriptive research methodology provides all study data in numerical form. In this study, the survey methodology and the regression procedure are combined. This study involved 237 students that were enrolled in the Cooperative Economics Study Program at Jakarta State University between 2017 and 2019. Data was gathered via a questionnaire. The concept is accepted since having an entrepreneurial ambition is linked to both a need for success and a propensity for taking risks.